DIETA E HÁBITO ALIMENTAR DE Apareiodon vittatus GARAVELLO, 1977, (CHARACIFORMES, PARADONTIDAE) ESPÉCIE ENDÊMICA DO RIO IGUAÇU, PR, BRASIL - MENESES, Cleiton; KASHIWAQUI, Elaine (ANAIS DO ENIC, 2022)
-